Prevalence and Antibiogram of Extended-Spectrum Beta-Lactamase Producing Gram-negative Bacteria Isolated from Septicemic Neonates in a Tertiary Care Hospital - Rahman, Tania; Begum, Momtaz; Sultana, Sharmeen; Shamsuzzaman, SM (KYAMC Journal, 2021)
Background: In recent years, Extended-spectrum beta-lactamase (ESBL) producing microorganisms have complicated treatment of infections due to resistance of ESBL producing strains to a wide range of antimicrobials. Objective: Target of this study was to determine the prevalence of ESBL producing gramnegative bacteria in neonatal sepsis cases and to reveal the antimicrobial susceptibility pattern of those isolated ESBL producers. Materials and Methods: This cross sectional study was carried out in Dhaka Medical College Hospital (DMCH) over a period of 12 months from January to December in 2016. Following isolation and identification of gram-negative bacteria from blood samples of suspected septicemic neonates, antimicrobial susceptibility test was performed by Kirby Bauer disk-diffusion method and ESBL producers were detected by Double Disk Synergy (DDS) test. Results: Among 52 Gram-negative bacteria isolated from 106 blood samples, 34.61% ESBL producers were detected and Enterobacter spp. (45%) was predominant followed by Klebsiella pneumoniae (33.33%). None of the ESBL producers was resistant to colistin and tigecycline. All ESBL producing Acinetobacter baumannii, 77.78% and 66.67% of ESBL producing Enterobacter spp and Klebsiella spp. respectively showed resistance to meropenem. All ESBL producers were resistant to piperacillintazobactam. Conclusion: Appropriate measures should be taken to prevent the spread of ESBL producing strains by combining strategies for infection prevention, control and rational use of antibiotics. KYAMC Journal Vol. 11, No.-4, January 2021, Page 171-175